Przedsiębiorczość zespołowa jako narzędzie rozwoju lokalnego - Wiatrak, Andrzej Piotr (Group Enterprise as a Tool of Local Development, 2006)
Cluster enterprise can be one of ways of development in local economy, which it results with prepared developmental strategies and instruments connected with their realisation. It accepting the correlation between exchanged questions as thesis of present elaboration were introduced the following questions: strategies of local development and their conditioning, team enterprise and conditioning of team working as well as aid of development of enterprise in local economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 664-671